Legenda geral do mapa ambiental de Londrina: ensaio metodológico de cartografia - Rosely Sampaio Archela; Nathália Prado Rosolém (Confins)
This methodological essay is part of a research that focus on achieving a reflection on the methodology cartographic of André Journaux (1984) for environmental cartography, from the analysis of work performed and directed by this researcher and the study of its specific legend. The first phase, presented in this article characterized by the legend proposal that will be used to represent the environmental dynamics of Londrina.